Undergraduate EFL learners’ preferences for three different types of written corrective feedback - Monera Almohawes (Frontiers in Education)
The present study examined undergraduate EFL learners’ preferences for three different types of written corrective feedback: direct, indirect, and metalinguistic. The participants were undergraduate students from various colleges at Hail University. A mixed-methods approach was employed, with data collected through a questionnaire and semi-structured interviews. The researcher sought to investigate learners’ preferences for direct, indirect, or metalinguistic written corrective feedback and the reasons behind these preferences. The results showed that most learners preferred direct written corrective feedback because it helped them improve their writing skills and was easier to understand. While the quantitative findings indicated that learners were uncertain about metalinguistic written corrective feedback, the qualitative responses suggested a preference for it, as it was perceived as an interesting, memorable, and enjoyable learning experience that motivated them to learn. The findings also revealed that learners did not prefer indirect written corrective feedback. The current study involves learners’ preferences which acknowledges the importance of their opinion in the learning process, leading to more effective and personalized language learning experiences. Future research could explore students’ preferences for written corrective feedback in relation to how new technology might affect these preferences.